Evaluation of oxidity resistance of milk-containing products based on blending of vegetable oils - Belemets, Tatiana; Radzievska, Irina; Tochkova, Oksana; Yushchenko (Gonchar), Natalia; Bandura (Kuzmyk), Uliana; Mykhalevych, Artur (My University, 2021)
It is known that one of the main causes of spoilage of fats (in particular vegetable fats), as well as products made with their use, is an increase in acid and peroxide numbers. Physicochemical indicators have a significant impact not only on the quality and organoleptic characteristics of the product, but also on its safety. For this purpose, the dependence of the indicators of acid and peroxide numbers of the created blend of vegetable oils in the technologies of milk-containing products during storage has been investigated. The object of research is experimental samples of a three-component blend of vegetable oils and milk fat isolated from milk-containing curd paste and milk-containing sour cream sauce. The subject of research is the dynamics of the growth of acid and peroxide numbers of samples and changes in their organoleptic quality indicators. The obtained data on the kinetics of oxidation of a blend of vegetable oils indicate that the increase in acid and peroxide numbers during the studied shelf life does not differ in intensity. The average threshold for an increase in acid and peroxide numbers is insignificant and amounts to 0.02–0.03 mgKOH/h and 0.2–0.21 mmol1/2O/kg for 5 days. In accordance with the obtained results of the kinetics of oxidation of the released fat of milk-containing curd paste, there is a slight increase in acid and peroxide numbers, namely: at the end of 7 days – up to 0.3 mgKOH/h and 1.9 mmol1/2O/kg, respectively, and in at the end of 10 days– up to 0.32 mgKOH/h and 2.3 mmol1/2O/kg. Based on the obtained results of the kinetics of oxidation of the released fat from the milk-containing sour cream sauce, there is a tendency to a gradual increase in the acid and peroxide numbers with an increase in the oxidation time. It is noted that the maximum values of acidic – 0.3 mgKOH/h and peroxide numbers – 2.2 mmol1/2O/kg at the end of the shelf life of 21 days are reached. According to the results obtained for the organoleptic evaluation of experimental samples of the blend and the released fat from milk-containing products, no significant changes were found during the studied shelf life.
Keywords: milk-containing curd paste; milk-containing sour cream sauce; blend of vegetable oils; acid number; кафедра біотехнології і мікробіології; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; кафедра технології консервування; кафедра технології ресторанної і аюрведичної продукції; кафедра технології молока і молочних продуктів